Does Random Selection of Commissioners Improve the Quality of Selected Candidates? An Investigation in the Italian Academia - Daniele Checchi; Silvia De Poli; Enrico Rettore (Institute of Labor Economics (IZA), 2017)
We study a reform occurred in Italy in 2008 in the formation of selection committees for qualifying as university professor. Prior to the reform members of the selection committees were elected by their peers, after the reform they have been randomly drawn. This policy was intended to increase the equality of opportunities of candidates via a reduction of the role played by connections to commissioners. Results show that the reform was ineffective in reducing the probability contribution of being an insider, but attenuated the impact of being connected to a commissioner without significantly raising the impact of scientific quality of candidates on the outcome of competitions. We also find that candidates internalised the changed environment and adapted their strategy of application.
Keywords: M51; I23; D82; J45; 330; university recruitment; incentives; negotiation; formal procedures